THE EFFECT OF ACCOUNTING INFORMATION SYSTEM QUALITY AND TRUST ON CUSTOMER SATISFACTION IN USING MOBILE BANKING WITH PERSONAL DATA SECURITY AS THE MODERATION - Anggraini, Dahlia Tri; Ajeng Radiska Febriola; Juita Tanjung; Septi Wulandari Chairina (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
Customer satisfaction plays a crucial role in encouraging continued use of financial services. This study examines the effect of Accounting Information System (AIS) quality and trust on customer satisfaction in mobile banking, with data security as a moderating variable. Primary data were collected through questionnaires distributed to mobile banking users at PT Bank XYZ (Persero), Jakarta, specifically at the Fatmawati branch. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 software. The results indicate that AIS quality and data security do not significantly affect customer satisfaction in mobile banking. In contrast, trust has a significant positive effect on customer satisfaction. Furthermore, the findings reveal that data security does not moderate the relationship between AIS quality and customer trust, which in turn does not influence customer satisfaction. These results highlight the dominant role of trust in shaping user satisfaction, indicating that the quality of accounting information systems and data security alone are insufficient to enhance the customer experience. The study contributes to the literature on mobile banking by emphasizing the importance of trust as a key determinant of customer satisfaction, and provides insights for banks to strengthen trust-building strategies in digital financial services.